Levamisole adulterated cocaine associated ANCA vasculitis: review of literature and update on pathogenesis. Issue 6 (2nd November 2018) - Jin, Qiuyu; Kant, Sam; Alhariri, Jihad; Geetha, Duvuru
ABSTRACT: Levamisole is an antihelminth drug and a common cocaine contaminant, present in an estimated 71% of cocaine samples in the US. Levamisole-contaminated cocaine has been linked to an ANCA-associated vasculitis with cutaneous, renal, and pulmonary manifestations. We report the case of a 46 year old woman with known cocaine exposure who presents with recurrent, large purpuric and maculopapular rash of the extremities and face and review existing cases of levamisole/cocaine-associated ANCA vasculitis, We summarize the clinical presentation, treatment, and outcomes of levamisole induced vasculitis. There is emerging research on pathogenesis relating to neutrophil extracellular traps (NETs). We review studies implicating role of NETs in the pathogenesis of levamisole induced vasculitis. Further research to explore the use of NETs as therapeutic targets in drug induced vasculitis is needed.